2022
DOI: 10.3389/fdgth.2022.847080
|View full text |Cite
|
Sign up to set email alerts
|

How Do Dental Clinicians Obtain Up-To-Date Patient Medical Histories? Modeling Strengths, Drawbacks, and Proposals for Improvements

Abstract: BackgroundAccess to up-to-date patient medical history is essential for dental clinicians (DCs) to avoid potential harm to patients and to improve dental treatment outcomes. The predominant approach for dental clinicians (DCs) to gather patients' medical history is through patient-reported medical histories and medical consults. However, studies reported varied concordance and reliability of patient-reported medical conditions and medication histories compared to the patient medical records and this process al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…The organization (data quality, environment, and equipment contamination) and lack of sufficient preparation in responding are some of the health information system challenges. (Li et al, 2022) 47 Qualitative The models for current approaches identified the people, resources, organizational aspects, workflow, and areas for improvement; while models of the HIE approach identified system requirements, functions, and processes that may be shared with software developers and other stakeholders for future development. (Lutfi et al, 2022) 428 Quantitative The influence of performance expectancy (PE), effort expectancy (EE) and facilitating conditions (FC), on intention toward mlearning use but did not support the significant influence of social influence (SI).…”
Section: Resultsmentioning
confidence: 99%
“…The organization (data quality, environment, and equipment contamination) and lack of sufficient preparation in responding are some of the health information system challenges. (Li et al, 2022) 47 Qualitative The models for current approaches identified the people, resources, organizational aspects, workflow, and areas for improvement; while models of the HIE approach identified system requirements, functions, and processes that may be shared with software developers and other stakeholders for future development. (Lutfi et al, 2022) 428 Quantitative The influence of performance expectancy (PE), effort expectancy (EE) and facilitating conditions (FC), on intention toward mlearning use but did not support the significant influence of social influence (SI).…”
Section: Resultsmentioning
confidence: 99%
“…16 To help alleviate these discrepancies, various strategies have been suggested, such as combining patient-reported medical histories and medical consultations, an integrated electronic health record containing a dental record module, and a regional healthcare information exchange. 58 Implementation of the electronic medical record has not resulted in the absence of discrepancies in medication lists. 59 Among the most common reasons for dental providers to seek medical consults, almost 40% are related to medication information and 1 out of every 4 requests concern medication lists.…”
Section: Discussionmentioning
confidence: 99%
“…Research programs aimed at evaluating outcomes in closing gaps for older adult populations confirmed that the use of an integrated health record was successful in alleviating deficiencies in preventive care (e.g., vaccinations) and disease management (e.g., Diabetic hemoglobin HbA1C monitoring) 95 . Record integration would help dental providers make quicker and better clinical decisions and ensure high quality care especially for older adults who have complex medical histories 96 . In 2018, 7 in 10 dentate adults aged 50 years or older reported having gone to a dentist in the past year.…”
Section: Innovations For the Prevention Of Oral Diseasementioning
confidence: 99%
“…95 Record integration would help dental providers make quicker and better clinical decisions and ensure high quality care especially for older adults who have complex medical histories. 96 In 2018, 7 in 10 dentate adults aged 50 years or older reported having gone to a dentist in the past year. Although COVID-19 has had a dramatic impact on care utilization, the youngest baby boomers are still part of the workforce and are highly likely to obtain dental insurance through their employers.…”
Section: Medical and Dental Integrationmentioning
confidence: 99%